The prevalence of pulp stones in the Kurdish population as a diagnostic tool in endodontic prognosis using Digital Orthopantomograph - Ahmed, Azhar Ghanim; Jalal, Ranj Adil; Mahmood, Mohammed Abdalla; Abdalrahim, Rukhosh Hasan (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Pulp stones (PSs) are calcified masses, found commonly in dental pulps of healthy, diseased, and even unerupted teeth. Objectives: Our study aims to determine the prevalence of PS in Kurdish adults using an orthopantomograph (OPG) and investigate the relationships between PSs with sex, age, tooth type, and dental arch/side. Patients and Methods: We examined 1,170 digital OPGs from Kurdish patients at the private Maxillofacial Radiology Center in Sulaimaniyah City, Iraq, were taken for various purposes between January and July 2023. A total of 31,598 teeth were examined to identify PSs. We collected patient data and determined correlations between the presence of PSs and various patient variables. Results: About 242 (20.68%) patients and 471 (1.49%) teeth had at least one stone. The prevalence of PS in the Kurdish population was 20.68% based on the total number of patients examined and it was 1.49% based on the total teeth examined. The PS frequently was found in those aged 45 years and more (50%) and the PS prevalence was higher in females (61%) than males (39%). The maxillary dental arches and molar teeth had the highest frequency of PS (p=0.000). Conclusions: In the Kurdish population, the prevalence of PSs was moderately high, particularly among females. PSs were most frequent in the maxillary arch and first molars, with incidence increasing with age.
Keywords: Pulp stone; orthopantomograph; endodontic prognosis; Kurdish population